A science-based investment due diligence & screening methodology co-developed with Africa Enterprise Challenge Fund (AECF) to assess CSA impact in their $20 million agribusiness in Africa window round 2 program - Wamicwe, Peter; Costa, Ciniro; Newman, Richard; Grosjean, Godefroy; Cosgrove, Bethany Emma (2023)
The Africa Enterprise Challenge Fund (AECF) identified and prioritized funding to CSA business models with the potential to implement and scale climate mitigation and adaptation practices. Using the AICCRA co-designed improved science-based approach for investment, due diligence and screening, AECF evaluated and recommend cost- effective implementation of CSA practices and monitoring of CSA impact post investment, thus catalyzing further funding into the sector.